Enhancing Seventh Graders' Vocabulary Mastery Trough the Use of Movies : A Quasi-Experimental Study - Landu, Miftahurrahma; Usman, Sriati; Patmasari, Andi; Anggreni, Afrillia (Journal of English Language and Education, 2025)
This study aims to investigate the effectiveness of using films as a learning medium to improve English vocabulary mastery in seventh-grade junior high school students. The methodology used is quasi-experimental with a pre-test and post-test design involving two groups, namely the experimental group and the control group. The sample size consisted of 64 students, divided equally into 32 students in the experimental group who were taught using films, and 32 students in the control group who were taught using conventional methods. The type of film used in the learning intervention was a short animated film that was story-oriented and had easy-to-understand dialogue, chosen for its relevance to the age and potential to attract students' interest. The main statistical analysis, specifically through an independent t-test, showed a statistically significant difference between the post-test scores of the two groups. These results indicate that the intervention using films resulted in a substantially higher increase in vocabulary mastery. Quantitatively, the experimental group showed an average increase (gain score) of 25% compared to the control group, which only showed an increase of 10%. This was proven by calculations using the SPSS 24 software system . Thus, the main conclusion of this study is that the use of films is an effective and efficient learning medium for improving English vocabulary mastery in seventh-grade junior high school students.